Nature of computation and communication : International Conference, ICTCC 2014, Ho Chi Minh City, Vietnam, November 24-25, 2014 : revised selected papers /: International Conference, ICTCC 2014, Ho Chi Minh City, Vietnam, November 24-25, 2014 : revised selected papers. (2016) - Unknown
No abstract available